PENEGAKAN HUKUM PIDANA DALAM PERLINDUNGAN KONSUMEN MUSLIM DARI PRODUK MAKANAN YANG TIDAK HALAL DI KOTA PEKANBARU - Beta Pandu Yulita; Erdianto '; Ledy Diana (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2016)
State of Indonesia is currently experiencing growth and development on industrial goods and services, be it large or small scale, with Opt participation of the Republic of Indonesia in the free trade agreement ASEAN Economic Community (AEC) this year, resulting in the Indonesian market beset with products import without having halal certificate and label, so we need an active role in oversight of government to protect Muslim consumers of non-kosher products and endangering. The purpose of this thesis, namely: First, enforcement of criminal law in the protection of Muslim consumers of food products that are not kosher in the city of Pekanbaru Second, obstacles to enforcing the law against food products that are not kosher in the city of Pekanbaru Third, efforts to overcome the obstacles encountered in enforcing the law against halal food products that are not in the city of Pekanbaru.From the research there are three main things that can be inferred. First, there is no law enforcement against food products that are not labeled halal in Pekanbaru, because food products are still in the market without experiencing interference from the relevant authorities, and no test of associated labor and the inspection of the food products. Second, obstacles to enforcing the law against food product not labeled halal in Pekanbaru there are 5 factors that cause namely, the vagueness of legislation in terms of the investigator investigators in charge of law enforcement, lack of effective cooperation between the relevant authorities, do not support the means and facilities, public ignorance of their rights and obligations, and changes in the legal culture of society, Third, efforts made to overcome these barriers is to provide an appeal to businesses to take care of halal certificates, coordinate with related MUI mandatory food using the halal label.Keywords: Law Enforcement - Consumer Protection - Labelling Halal